Retama monosperma (L.) Boiss.: A review of its uses in traditional medicine, chemical constituents, and pharmacologic activities - Fatima Zahra Benkhouili; Amina Moutawalli; Hanane Benzeid; Anass Doukkali; Ahmed Zahidi (Elsevier, 2022)
Introduction: Retama monosperma (L.) Boiss., which belongs to the Retama genus, is a medicinal plant endemic to the Mediterranean basin. It is used in traditional medicine to treat various diseases such as skin diseases, diabetes, rheumatism, and hypertension. In this review, we highlighted previous information on the taxonomy, botanical description, geographical distribution, uses in traditional medicine, chemical composition, and pharmacologic activities of Retama monosperma (L) Bioss. Methods: The data on Retama monosperma (L) Bioss was collected using the scientific research databases PubMed, Scopus, and Web of Science. The compiled bibliography contains twenty-one references. The Plant List and the "Inventaire National du Patrimoine Naturel" were used to authenticate the scientific names. The information presented in this paper summarises the phytochemicals, uses in traditional medicine, and pharmacologic properties of Retama monosperma (L) Bioss. Results: In traditional medicine in the Mediterranean region, Retama monosperma (L) Bioss is used to treat various diseases including diabetes, abortive, rheumatism, and hypertension. Overall, these studies show that the extracts of different parts of Retama monosperma (L) Bioss have five main pharmacologic activities, such as anti-cancer, anti-oxidant, anti-inflammatory, anti-fungal, and anti-aging activities. The phytochemical analysis by GC/MS, HPLC/MS, and NMR of the essential oil and the extracts of Retama monosperma (L) Bioss revealed the presence of different classes of secondary metabolites bioactive such as cyclitols, alkaloids, flavonoids, terpenes, and sterols. In this study, we inventoried 60 compounds isolated and identified from different extracts of Retama monosperma (L) Bioss. Conclusions: Many aspects of Retama monosperma (L) Bioss extracts and their secondary metabolites have not been investigated; further studies on toxicity and clinical activity are needed to explore the untapped potential of this plant.